Sigmoid Carcinoma in an Inguinal Hernia: A Blessing in Disguise?. (5th December 2013) - Salemans, P. B.; Vles, G. F.; Fransen, S. A. F.; Smeenk, R. M.
Abstract : Colorectal cancer is a rising problem, as the incidence increases with age. In most cases the goal of treatment is oncological resection followed by adjuvant chemotherapy in order to optimize the survival. In this case report we present a 93-year-old patient with a sigmoid carcinoma inside an irreducible inguinal hernia, which was diagnosed prior to surgery. We chose to perform a sigmoid resection through an oblique inguinal incision as a safer alternative to laparotomy.